2014
DOI: 10.1007/s10637-014-0179-1
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II study with ruthenium compound NAMI-A and gemcitabine in patients with non-small cell lung cancer after first line therapy

Abstract: NAMI-A administered in combination with gemcitabine is only moderately tolerated and less active in NSCLC patients after first line treatment than gemcitabine alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
265
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 343 publications
(273 citation statements)
references
References 55 publications
4
265
0
4
Order By: Relevance
“…It is doubtful that NAMI-A will be used as a mono-therapy for the treatment of human cancers and, thus, combination schedules with other antitumor drugs represent the optimum clinical approach. Indeed, the second clinical study performed with NAMI-A, following a phase I in which pharmacokinetic and host toxicity was defined, was performed in combination with gemcitabine for the treatment of metastasized NSCLCs [16]. This clinical study was selected because preclinical tests suggested a pronounced activity against lung metastases (Data on file, Callerio Foundation Onlus) and two patients with NSCLC in the previous phase I study showed prolonged disease stabilization [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is doubtful that NAMI-A will be used as a mono-therapy for the treatment of human cancers and, thus, combination schedules with other antitumor drugs represent the optimum clinical approach. Indeed, the second clinical study performed with NAMI-A, following a phase I in which pharmacokinetic and host toxicity was defined, was performed in combination with gemcitabine for the treatment of metastasized NSCLCs [16]. This clinical study was selected because preclinical tests suggested a pronounced activity against lung metastases (Data on file, Callerio Foundation Onlus) and two patients with NSCLC in the previous phase I study showed prolonged disease stabilization [15].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, NAMI-A completed a phase I/II study in combination with gemcitabine as a second line treatment for metastatic non-small cell lung cancer (NSCLC) [16]. The antimetabolite, gemcitabine, is one of the principal drugs used against NSCLC [17,18], frequently in combination with platinum-based drugs [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such complexes, including the indazolium ruthenium complex KP1019 (Fig. 17) and NAMI-A, have undergone phase I and II clinical evaluation for cancer with very limited side effects [193,196,205,230,[234][235][236][237]. Ru(II) complexes such as [RuCl 2 (2-phenylazopyridine) 2 ] (Fig.…”
Section: Cancermentioning
confidence: 99%
“…Unlike platinum, with which, after more than 50 years, it still seems impossible to develop compounds to significantly outdo the potent antitumour activity of cisplatin, ruthenium compounds offer a generally accepted lower host toxicity [4,5] and an innovative mechanism of antitumour activity [6][7][8]. Among these new me-too drugs, imidazolium trans-imidazoledimethylsulphoxidetetrachlorido ruthenate (nicknamed NAMI-A) is the first in this class of drugs used to treat the metastatic non-small cell lung cancer (NSLCL) in humans in a second-line therapy in combination with gemcitabine [9]. NAMI-A is endowed with a unique ability to act against the metastases of solid tumours without necessarily reducing the tumour at its primary site [10,11], emphasizing the possibility of its being used in many chemotherapy protocols, typically applied in patients to prevent the formation of, or reduce the bulk of, the disseminated disease.…”
Section: Introductionmentioning
confidence: 99%